MODERN POSSIBILITIES OF IMPORT SUBSTITUTION IN THE TREATMENT OF PAIN SYNDROME IN CANCER P ATIENTS - G. R. Abuzarova; G. S. Alekseeva; R. R. Sarmanaeva; L. V. Dushakova (Исследования и практика в медицине, 2015)
Objective. To evaluate the efficacy and safety of prosidol in cheek tablets in the treatment of chronic pain syndrome in cancer patients.Material and methods. The study was conducted at 152 cancer patients with chronic pain syndrome caused by  malignant neoplasms. The objectification of pain intensity was conducted on a 5 — point verbal scale assessments (SVA), assessed the state of physical activity of patients on a 5‑point scale ECOG, objectified the mental status and a night’s sleep: 0‑no pain; 1 — slight pain; 2 — moderate pain; 3 — severe pain; 4 points unbearable pain. We registered the duration of analgesic effect of prosidol, calculated single and daily doses of analgesic in the dynamics on the stages of therapy and its side effects. The results of the study were assessed on stages: 1 — initial, before treatment, 2 — first day of therapy, 3 — completion of the selection of doses of analgesic (3–4 days), 4 — a week after the start of treatment, 5–2 weeks after the start of treatment, 6 — at the end of the 3rd week of treatment.Results. Initial single dose of buccal prosidol (20 mg) caused effective analgesia after 10 to 45 (21,3+8,9) minutes after the first dose and lasted from 1 to 8 (6,0+1,8) hours: 21.8% of patients complete elimination of pain (more than 50% from baseline); in 63.6% of the pain was reduced by 30–50%; reduction of pain less than 30% — in 14.6% of patients. In General, a significant decrease in the intensity of pain with 2,47+0.37 to 0.5 to+0.30 VAS score (p<0.05). The failures of the drug were observed. All patients continued prosidol therapy after a 3‑week study period. The initial average daily dose of prosidol was 82.2 + 9,7 mg; 1 week of therapy — 112,3+16 mg, by the end of the 3rd week increased to 148,2+57 mg/day mg Tolerability was judged as good. Side effects: drowsiness and nausea most noted for 1–3 days of therapy was expressed moderately or weakly in 85% of patients (drowsiness of 62.3%, nausea is 27.3%, vomiting in 15%; dry mouth is 65.5%, dizziness) to 27.6%). Night sleep was stabilized at 85% (relative to 13% in the initial stage); the number of patients with symptoms of depression decreased in 1.8–2.2 times.Conclusion. Buccal Procidol in a daily dose of from 60 to 200 mg provides effective analgesia in the majority of cancer patients with moderate to strong chronic pain at moderately pronounced side effects which are not dangerous, respond well to medical treatment. Procida in sublingual tablets possesses the basic properties required of modern medicine to opioid therapy for chronic cancer pain: it is effective, safe, better tolerated than other drugs,convenient for the independent application of patients in outpatient and home. The lack of buccal prosidol is the short duration of effects (average 4 hours).